2019
DOI: 10.1111/1758-2229.12736
|View full text |Cite
|
Sign up to set email alerts
|

Consistency in microbiomes in cultures of Alexandrium species isolated from brackish and marine waters

Abstract: Summary Phytoplankton and bacteria interactions have a significant role in aquatic ecosystem functioning. Associations can range from mutualistic to parasitic, shaping biogeochemical cycles and having a direct influence on phytoplankton growth. How variations in phenotype and sampling location, affect the phytoplankton microbiome is largely unknown. A high‐resolution characterization of the bacterial community in cultures of the dinoflagellate Alexandrium was performed on stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…The alteration or substitution of local microbial community was demonstrated to cause noteworthy changes in saxitoxin production by the athecate dinoflagellate G. catenatum [118]. This outcome is in agreement with the discovery of a later investigation, in which a few groups of bacteria were found to be present consistently among several strains of A. ostenfeldii, A. minutum, and A. tamarense [119]. The fascinating coexistence of dinoflagellates and bacteria in their phycosphere even led to the formulation of theories of saxitoxin biosynthesis by symbiotic bacteria living within the dinoflagellates.…”
Section: Metabolomics Within the Context Of Saxitoxin Biosynthesis: Asupporting
confidence: 87%
“…The alteration or substitution of local microbial community was demonstrated to cause noteworthy changes in saxitoxin production by the athecate dinoflagellate G. catenatum [118]. This outcome is in agreement with the discovery of a later investigation, in which a few groups of bacteria were found to be present consistently among several strains of A. ostenfeldii, A. minutum, and A. tamarense [119]. The fascinating coexistence of dinoflagellates and bacteria in their phycosphere even led to the formulation of theories of saxitoxin biosynthesis by symbiotic bacteria living within the dinoflagellates.…”
Section: Metabolomics Within the Context Of Saxitoxin Biosynthesis: Asupporting
confidence: 87%
“…This notion is similar to previous work on Prorocentrum (Wang et al, 2017;Kim et al, 2021), Alexandrium spp. (Sörenson et al, 2019), and Symbiodiniacean species (Lawson et al, 2018;Nitschke et al, 2020). In the present study, we found that Labrenzia and Muricauda were the most abundant and common bacteria shared across all cultures.…”
Section: Identification Of Core (Constitutive) Component Of Gambierdi...supporting
confidence: 59%
“…This study also showed that algal‐attached communities in seawater are different from bulk particle‐associated communities, indicating that phycosphere communities are specific and distinct from the regional species pool. The Rhodobacteraceae and Flavobacteriaceae reported here are common members of dinoflagellate microbiomes, whereas Planctomycetes are rare or absent in dinoflagellate microbiome sequence sets (Hasegawa et al ., ; Severin and Erdner, ; Sörenson et al ., ). Crenn and colleagues () compared microbiomes of diatoms from cultures and environmental samples, and reported lower diversity in the former.…”
Section: Discussionmentioning
confidence: 97%